2012
DOI: 10.1016/j.neuropsychologia.2012.10.010
|View full text |Cite
|
Sign up to set email alerts
|

How does the hippocampal formation mediate memory for stimuli processed by the magnocellular and parvocellular visual pathways? Evidence from the comparison of schizophrenia and amnestic mild cognitive impairment (aMCI)

Abstract: Paired associates learning is impaired in both schizophrenia and amnestic mild cognitive impairment (aMCI), which may reflect hippocampal pathology. In addition, schizophrenia is characterized by the dysfunction of the retino-geniculo-striatal magnocellular (M) visual pathway. The purpose of this study was to investigate the interaction between visual perceptual and memory dysfunctions. We administered a modified version of the CANTAB paired associates learning task to patients with schizophrenia (n=20), aMCI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…Participants with memory deficits showed decreasing hippocampal activation with increasing memory load, whereas normal controls showed the opposite pattern. In addition, Kéri et al ( 2012 ) showed that impairment on CANTAB PAL was correlated with hippocampal volume loss in both schizophrenia and mild cognitive impairment. The hippocampus also appears to be involved in the rat version of the task as acute inactivation after dPAL acquisition has been shown to impair performance (Talpos et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Participants with memory deficits showed decreasing hippocampal activation with increasing memory load, whereas normal controls showed the opposite pattern. In addition, Kéri et al ( 2012 ) showed that impairment on CANTAB PAL was correlated with hippocampal volume loss in both schizophrenia and mild cognitive impairment. The hippocampus also appears to be involved in the rat version of the task as acute inactivation after dPAL acquisition has been shown to impair performance (Talpos et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…People with mild cognitive impairment (MCI) have decreased hippocampal activation with increasing memory load, whereas by contrast healthy controls show the opposite pattern ( De Rover et al., 2011 ). Furthermore, impaired performance on the CANTAB PAL correlates with hippocampal volume loss in MCI ( Kéri, Szamosi, Benedek, & Kelemen, 2012 ). A recent neuroimaging study has also shown that MTL structures play an important role in associating different stimuli (in this case objects and scenes) when retrieving them from memory ( Staresina, Cooper, & Henson, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the magnocellular origin of contrast sensitivity alteration in SCZ has been debated (Skottun and Skoyles, 2007, 2011) because the magnocellular system shows a considerable overlap with other cells in the visual system regarding contrast and SF response. Nevertheless, evidence suggests that the cortical processing of low SFs is compromised in SCZ (Martínez et al, 2008; Kéri et al, 2012; Calderone et al, 2013), and that low SF achromatic gratings activate the putative magnocellular layers of the human lateral geniculate nucleus (Denison et al, 2012). The rapid development of high-resolution imaging techniques capable of identifying and visualizing the magnocellular layers may provide answer to this debate question.…”
Section: Discussionmentioning
confidence: 99%